2016
DOI: 10.3390/rs8040335
|View full text |Cite
|
Sign up to set email alerts
|

On the Added Value of Quad-Pol Data in a Multi-Temporal Crop Classification Framework Based on RADARSAT-2 Imagery

Abstract: Polarimetric SAR images are a rich data source for crop mapping. However, quad-pol sensors have some limitations due to their complexity, increased data rate, and reduced coverage and revisit time. The main objective of this study was to evaluate the added value of quad-pol data in a multi-temporal crop classification framework based on SAR imagery. With this aim, three RADARSAT-2 scenes were acquired between May and June 2010. Once we analyzed the separability and the descriptive analysis of the features, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
5
31
2
Order By: Relevance
“…Results showed that rapeseed achieved the best PA results (>95%) in all scenarios, whereas barley achieved the second highest PA's, ranging from 92.1% to 95.3%. The user's accuracy (UA) of both crops was above 85% for all scenarios tested and achieved 100% for rapeseed in scenarios A and D. The results reported in this study for rapeseed agree with those found by Larrañaga and Álvarez-Mozos [35]. Cereals (i.e., wheat and barley) normally show a similar behaviour during the growing season due to their very similar plant structure and phenology, which causes difficulty in separating them based on their backscatter characteristics.…”
Section: Land-cover Classification and Accuracy Assessmentsupporting
confidence: 90%
See 2 more Smart Citations
“…Results showed that rapeseed achieved the best PA results (>95%) in all scenarios, whereas barley achieved the second highest PA's, ranging from 92.1% to 95.3%. The user's accuracy (UA) of both crops was above 85% for all scenarios tested and achieved 100% for rapeseed in scenarios A and D. The results reported in this study for rapeseed agree with those found by Larrañaga and Álvarez-Mozos [35]. Cereals (i.e., wheat and barley) normally show a similar behaviour during the growing season due to their very similar plant structure and phenology, which causes difficulty in separating them based on their backscatter characteristics.…”
Section: Land-cover Classification and Accuracy Assessmentsupporting
confidence: 90%
“…When Sentinel-1 dual-pol SAR data were used as input for the classification, the second-best accuracy (87.1%) was obtained, whereas using dual-pol RADARSAT-2 data (scenario F) provided a similar overall accuracy (86%). The accuracy of the dual-pol RADARSAT-2 data in the general computation of this study showed higher accuracy than previous studies in the literature [35,39]. From RADARSAT-2 scenarios, the accuracies of 89.1% and 86.6% for scenarios D and A, respectively, were quite similar; however, D required many more SAR images and parameters than A to achieve this small 2.5% improvement of accuracy.…”
Section: Land-cover Classification and Accuracy Assessmentcontrasting
confidence: 46%
See 1 more Smart Citation
“…Earth observation satellites that monitor and regularly revisit cropland are inexpensive and excellent data sources that provide full spatial detailed information for crop mapping [8,9]. In recent decades, many studies have focused on crop monitoring with optical [10-14] and synthetic aperture radar (SAR) images [1,[15][16][17][18]. Multitemporal and time series data are powerful tools for identifying different crops and handling the problem of spectral similarity in heterogeneous underlying surfaces in single-period imagery [19][20][21][22][23].…”
mentioning
confidence: 99%
“…Optical remote sensing data with high resolution, such as data extracted from remote sensing image indices and other high-quality land cover data products, are the major datasets used for urban information extraction [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], and such data are far superior to those of DMSP-OLS in terms of image resolution. However, most of these data products have limited temporal coverage and present limited usefulness for a dynamic analysis at large scales.…”
Section: Introductionmentioning
confidence: 99%